The Influence Of Organizational Culture And Organizational Commitment On Employee Work Effectiveness With Decision Making As A Mediating Variable - Muda Harahap, Zainy Cholis (Perkumpulan Konsultan Manajemen Pendidikan Indonesia (PKMPI), 2023)
This research aims to determine whether organizational culture and organizational commitment have a positive and significant effect on employee work effectiveness and to find out how decision making mediates the influence of organizational culture and organizational commitment on employee work effectiveness. This research was carried out using a questionnaire method, namely data collection which was carried out by distributing a list of written questions given to the subjects to be studied, namely 167 respondents, namely 167 employees. The data analysis technique used in this research is SEM (Smart Partial Square) PLS analysis with a significance level of 5%. The results obtained show that Organizational Culture has a positive and significant influence on Work Effectiveness with an Original Sample (O) value of 0.272 so that the influence of organizational culture is 27.2% and positive. However, Organizational Commitment does not have a positive and significant influence on Work Effectiveness with an Original Sample value of -0.033, so it can be concluded that commitment has no influence and has a negative relationship of -3.3%. Furthermore, Decision Making mediates the influence of Organizational Culture on Work Effectiveness positively and significantly, this shows that decision making is able to improve organizational culture in influencing work effectiveness by 18.6%. And Decision Making mediates the influence of Commitment on Work Effectiveness positively and significantly, this shows that decision making is able to increase employee commitment in influencing work effectiveness by 38.3%.